Representações da vida feminina em um acervo de imagens fotográficas do Museu da Baronesa, Pelotas/RS: 1880 a 1950 - Montone, Annelise Costa (2011)
This research aims to analyze a set of electrostatic copies of photographs stored in the Museu Municipal Parque da Baronesa, in Pelotas city, RS. We pay special attention to female portraits, insofar as they dialogue with the narratives of this museal space designed to the period between 1880 and 1950. In the nineties these images were part of two short duration exhibits dealing with fashion and childhood. This municipal museum maintains the type of a historic house museum from the times it belonged to Antunes Maciel family. It holds therefore a strong link with female figures for the sake of three female generations that inhabited the house. The collections are formed by the building itself, personal and decorative objects, furniture, textile, private documents, books and original photographs, which bring representations of private space and uses of local society. We interpreted the material in the scope of cultural history of women, collections, representations, memory and photographs, as well as private documents and academic monographs concerning Antunes Maciel family